تطبيق طريقة الغناء على حفظ المفردات لدى طالبات الصف السابع بمدرسة فرغوروان معلمات المتوسطة الإسلامية الأهلية جومبانج - Amalia Agata, Rona; Arif Setyabudi, Muhammad (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
Language is a communication tool for a person, to learn a new language requires the correct learning method so that he can achieve the goal of the intention to learn. Memorizing vocabulary Arabic important in understanding the most complex Arabic texts, the ability to speak, write and understand the sources of Islamic legal teachings such as the Qur'an and Hadith. This study uses a type of descriptive research, which is research that aims to describe existing phenomena, namely natural phenomena or man-made phenomena, or those used to analyze or describe the results of the subject. Applying the singing method, which is to introduce new singing to students and facilitate their singing of the song in full and verse to verse, it is hoped that you will be able to add references and improve the quality of language learning Arabic, especially in vocabulary learning.